Pathological granuloma fibrosis induced by agar-embedded Mycobacterium abscessus in C57BL/6JNarl mice - Yang, Shiu-Ju; Hsu, Chih-Hao; Lai, Chi-Yun; Tsai, Pei-Chu; Song, Yung-Deng; Yeh, Chang-Ching; Chen, Yih-Yuan; Dou, Horng-Yunn (Frontiers in Immunology, 2023)
Introduction Pulmonary granuloma diseases caused by Mycobacterium abscessus (M. abscessus) have increased in past decades, and drug-resistance in this pathogen is a growing public health concern. Therefore, an animal model of chronic granuloma disease is urgently needed. Methods In this study, M. abscessus embedded within agar beads (agar-AB) was used to develop such a model in C57BL/6JNarl mice. Results Chronic infection was sustained for at least 3 months after agar-AB infection, visible granulomas spread in the lungs, and giant cells and foamy cells appeared in the granulomas. More importantly, pulmonary fibrosis progressed for 3 months, and collagen fibers were detected by Masson trichrome staining. Further, inducible nitric oxide synthase (iNOS) was highly expressed within the alveolar space, and the fibrosis-mediator transforming growth factor beta (TGF-β) began to be expressed at 1 month. Hypoxia-inducible factor (HIF-1α) expression also increased, which aided in normalizing oxygen partial pressure. Discussion Although the transient fibrosis persisted for only 3 months, and the pulmonary structure resolved when the pathogen was cleard, this pulmonary fibrosis model for M. abscessus infection will provide a novel test platform for development of new drugs, regimens, and therapies.